Fenomena Pencemaran Lingkungan: Dampak Pencemaran Udara Terhadap Kesehatan - Elsa Sulistiani; Ageng Saepudin Kanda S (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Air pollution is an important problem that can threaten human life. Factors that cause air pollution come from the incomplete combustion of fuel produced by factory machines, power plants and motorized vehicles. Metabolism in the bodies of living creatures is impossible without oxygen from the air. Every adult requires at least 33 m² of air changes per hour, however, oxygen obtained from urban air is often mixed with various pollutants. Among the air pollutants most commonly found in urban air, especially those originating from the transportation sector, are Pb and CO.